Post-DIscharge Complications of Dental Treatment in General Anesthesia Performed in a Day-Care Service - Vlaho Brailo; Bernard Janković; Dragana Gabrić; Marin Lozić; Vasilije Stambolija; Danica Vidović Juras; Željko Verzak (University of Zagreb. School of Dental Medicine, 2021)
Objective: To review the frequency and management of post-discharge complications in patients who underwent dental treatment in general anesthesia (GA) in a day-care surgery setting and identify the factors that increase the risk for these complications. Material and methods: Anonymous questionnaire was sent to parents/caregivers of patients who underwent full mouth restoration in GA at our institution between 1 st January 2017 and 31 st July 2019. Demographic and clinical data of patients as well as the data about the occurrence and management of complications were collected. Results: Sixty-six parents/caregivers (30.5%) responded to the questionnaire. Most frequent complications were drowsiness and pain in 40(60.6%) patients. Complications were managed by parents or caregivers with conservative measures at home in 57(91.9%) cases. Phone consultation with dentist was required in 5(8.1%) cases. One patient (1.6%) was readmitted. Younger age and diagnosis were associated with increased risk for drowsiness. Conclusion: Post discharge complications of dental treatment in GA in a day-care service are common and they can be managed by parent/caregiver with conservative measures at home. The rate of readmission is low. Dental treatment in GA in a day-care service is a safe procedure that can be performed with acceptable risk in carefully selected patients.